Human resource management - Phillips, Jean M.; Gully, Stanley Morris (Mason, Ohio : Chicago Business Press, 2019)
The focus of this book is on developing students' personal and managerial skills by (1) Helping students understand the role of HR in organizational effectiveness as well as their personal career success; (2) Enabling students to understand how to flexibly apply the HR concepts that are appropriate for different problems or situations, and how HR both influences and is influenced by business strategy; and (3) Creating an understanding of the HR context by embedding the important concepts of ethics, diversity, competitive advantage, and the global context throughout the book. This highly readable book will help students understand how to use HR to hire, develop, motivate, and retain the right people and bring out the best in employees to execute the company's business strategy. It is intended for anyone who is or who might become a manager or an HR professional. By developing readers' competence and confidence in using important HR skills, this book will help anyone become a more effective manager through a better use of HR tools. Because most students learn more easily when they see the applicability of concepts to real life situations, HUMAN RESOURCE MANAGEMENT provides numerous current company examples throughout the book. A book-long integrated case supplemented with interactive online videos develops students' personal skills and gives them some experience in applying various HR concepts. The case and videos reinforce the relevance of the textbook material and make the content even more understandable.
PART ONE The Importance and Context of Human Resource Management -- Chapter 1 Strategic Human Resource Management -- Chapter 2 The Role of Human Resource Management in Business -- Chapter 3 The Legal Context of HRM -- PART TWO Planning and Staffing -- Chapter 4 Analyzing Work and Human Resource Planning -- Chapter 5 Sourcing and Recruiting -- Chapter 6 Selection and Hiring -- PART THREE Training and Performance Management -- Chapter 7 Training and Development -- Chapter 8 Performance Management -- PART FOUR Managing Total Rewards -- Chapter 9 Base Compensation -- Chapter 10 Incentives -- Chapter 11 Benefits -- PART FIVE Managing the Work Environment and Increasing Employee Engagement -- Chapter 12 Creating a Healthy Work Environment -- Chapter 13 Creating Positive Employee-Management Relations -- Chapter 14 Managing Engagement and Turnover.
Includes bibliographical references and index.
Keywords: Personnel management; Management; Management; Personnel management